A JAR of Chirps: The Gymnotiform Chirp Can Function as Both a Communication Signal and a Jamming Avoidance Response - Field, Caitlin E.; Petersen, Thiago Alexandre; Alves-Gomes, José A.; Braun, Christopher B. (Frontiers in Integrative Neuroscience, 2019)
The weakly-electric gymnotiform fish produce a rhythmic electric organ discharge (EOD) used for communication and active electrolocation. The EOD frequency is entrained to a medullary pacemaker nucleus. During communication and exploration, this rate can be modulated by a pre-pacemaker network, resulting in specific patterns of rate modulation, including stereotyped communication signals. One well-known signal is the chirp, a brief upward frequency sweep, usually lasting less than 500 ms. The abrupt change in frequency has dramatic effects on phase procession between two signalers. We report here on chirping in Brachyhypopmus cf sullivani, Microsternarchus cf bilineatus Lineage C, and Steatogenys cf elegans during conspecific playback experiments. To further explore the maturation of chirps, individual Steatogenys were implanted with DiHydro-Testosterone (DHT) and recorded repeatedly over the subsequent 4 weeks. In Steatogenys, chirp intensity increased after DHT treatment in both males and females in a dose-dependent manner. The most extreme chirps culminate in tens to hundreds of milliseconds of a low-voltage hash produced by unsynchronized firing of electrocytes. We also report on a similar ‘hushing silence’ during interruptions in Microsternarchus. Chirps are widely used in electronic communications systems, sonar, and other man-made active sensing systems. The brevity of the chirp, and the phase disruption it causes, makes chirps effective as attention-grabbing or readiness signals. This conforms to the varied assigned functions across gymnotiforms, including pre-combat aggressive or submissive signals or during courtship and mating. The specific behavioral contexts of chirp expression vary across species, but the physical structure of the chirp makes it extremely salient to conspecifics. Chirps may be expected in a wide range of behavioral contexts where their function depends on being noticeable and salient. Further, in pulse gymnotiforms, the chirp is well structured to comprise a robust jamming signal to a conspecific receiver if specifically timed to the receiver’s EOD cycle. Microsternarchus and Steatogenys exploit this feature and include chirps in dynamic jamming avoidance behaviors. This may be an evolutionary re-use of a circuitry for a specific signal in another context.